2021
DOI: 10.3390/ijerph18137192
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Characteristics and Cancer Survivorship: An Overview of the Current Literature on Neighborhood Landscapes and Cancer Care

Abstract: There is a growing literature on the association between neighborhood contexts and cancer survivorship. To understand the current trends and the gaps in the literature, we aimed to answer the following questions: To what degree, and how, has cancer survivorship research accounted for neighborhood-level effects? What neighborhood metrics have been used to operationalize neighborhood factors? To what degree do the neighborhood level metrics considered in cancer research reflect neighborhood development as identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 93 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…To the best of our knowledge, there are only two reviews available on our evaluated association and none systematically evaluated the evidence [4,5]. Our review included 18 studies, the previous scoping review [5] included only half of the studies which we included in the review.…”
Section: Accepted Manuscript / Clean Copy 28mentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there are only two reviews available on our evaluated association and none systematically evaluated the evidence [4,5]. Our review included 18 studies, the previous scoping review [5] included only half of the studies which we included in the review.…”
Section: Accepted Manuscript / Clean Copy 28mentioning
confidence: 99%
“…Emerging evidence suggests a variety of health beneficial effects of greenspace (which has been defined by the U.S. Environmental Protection Agency as "land that is partly or completely covered with grass, trees, shrubs, or other vegetation" [3]). The evidence on the association between exposure to greenspace and cancer is still emerging compared with other health outcomes [4,5]. The available literature on this association is also inconsistent, while some studies have found a beneficial association for greenspace [6][7][8], others have reported an increased risk of cancers associated with this exposure [9,10], or have not observed any associations [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence is still emerging, the psychosocial distress and physical wellbeing of cancer survivors was wide-ranging, exacerbated, and strongly stressed the need for drastic changes to cancer survivorship care in terms of frequency, type and mode of care delivery [26]. The main themes addressed in neighbourhood environment-related cancer survivorship care research are focused across survival disparities, primary care, and weight management, followed by quality of life and environmental exposure [27]. Scoping evidence shows how built environment features regarding urban design, land use, spatial accessibility and housing socioeconomic status are related to risk factors of cancer such as screening adherence, residential mobility, diet patterns, contaminated water and air quality [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Scoping evidence shows how built environment features regarding urban design, land use, spatial accessibility and housing socioeconomic status are related to risk factors of cancer such as screening adherence, residential mobility, diet patterns, contaminated water and air quality [28,29]. However, the correlate and causal relationships of built environment, namely housing design and environmental characteristics, cancer survival outcomes and care, and psychological wellbeing and mental comorbidities are understudied [27,29]. The individual's systemic chronic inflammatory burden has been postulated as a potential driver for multiple pathologies, including psychiatric diseases, and as a clinical predictor of multimorbidity [30].…”
Section: Introductionmentioning
confidence: 99%